MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PELUANG DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TIPE NUMBERED HEAD TOGETHER (NHT) DI KELAS VIIIᴅ SMP NEGERI 1 TIAKUR - Petrusz, Sigine; Molle, Juliana Selvina; Inuhan, Michael (Sora Journal of Mathematics Education, 2023)
This research aims to determine whether there is an increase in student learning outcomes SMP Negeri 1 Tiakur class VIII is taught using the Numbered Head Together (NHT) learning model, on opportunity material. The type of research used is Class Action Research (PTK). This can be seen from the results of the final test of cycle I where 8 students obtained minimum completeness criteria (KKM) or obtained a score of ≥70 with a presentation of 29.63%. Then in cycle II there were 23 students who obtained the minimum completeness criteria (KKM) or students who obtained a score ≥70 with a presentation of 85%. Based on the completion of cycle I and cycle II, there was an increase from cycle I to cycle II of 55.37%.